Virtuous cycles of learning: Redesigning testing during the digital re volution - Dawson, Theo; Stein, Zachary (2011)
This paper explores positive new directions for the future of educatio nal testing by examining trends at the interface of the learning scien ces and advances in educational technologies. A brief history of the r elation between testing and technology sets the stage for a look at em erging “edu-tech” trends and what these might mean for the future of t esting. This historical-critical look at past and present testing prac tices reveals that the learning sciences have been less influential in shaping the growth of testing infrastructures than cumulative advance s in technology that have enabled large-scale standardization and auto mation. We argue that during the current “digital revolution” the lear ning sciences ought to assume more responsibility for shaping the adop tion of new testing technologies. We propose a set of principles that, if followed, would move tomorrow’s testing infrastructures toward lea rning-centric design. Combining the affordances of new digital technol ogies with advances in our understanding of learning make it possible to build tests that promote multi-level learning in educational system s, catalyzing virtuous cycles of learning for everyone they affect—stu dents, teachers, school leaders, policy makers, and researchers. The D iscoTest™ Initiative is presented as a reform effort that is guided by these design principles, serving as an example of positive new possib ilities for testing at the interface of the learning sciences and new educational technologies.